Java™ 6 Platform Revealed - Zukowski, John (Apress, 2012)
So you like living on the bleeding edge and want to learn about Java 6, aka Mustang. Welcome. What you hold in your hands is a look at the newest features of the early access version of Mustang. Working through the early access releases from Sun, I’ve painfully struggled through the weekly drops and demonstrated the latest feature set to help you decide when or if it is time to move to Java 6. OK, maybe it wasn’t that painful. In any case, many of these new features make the transition from Java 5 (or earlier) to Java 6 the obvious choice.